Solar-powered irrigation as a curse for vulnerable water basins? A community case study using the water–energy–food security nexus - Aklan, Musaed; Lackner, Helen; Al-Saidi, Mohammad (Frontiers in Water, 2025)
The rise of solar-powered irrigation systems (SPIS) has shown promise in several developing countries. However, there is increasing concern about the consequences of easy access to energy in vulnerable groundwater basins. The agricultural sector in water-scarce Yemen relies heavily on groundwater resources, with solar energy recently enabling groundwater extraction for irrigation during the ongoing political instability. This community case study discusses the role of solar-powered irrigation systems (SPIS) within the water–energy–food security nexus (WEF-Nexus), based on community practices in the Sana’a Basin, Yemen. Using field surveys and expert perceptions, it highlights tradeoffs and repercussions associated with increased use of SPIS. Although farmers have embraced SPIS, capital investment costs are still the biggest obstacle to acquiring this technology. The increased use of SPIS will impact water use and cropping patterns, and can thus have long-term impacts on water security, food production, and equity issues. This paper proposes considerations for governance and policy to advance overall integrated water management and regulation of groundwater usage driven by SPIS. Establishing suitable frameworks for water extraction utilizing renewable energy can support the conservation of groundwater reserves and safeguard livelihoods under water scarcity exacerbated by the ongoing conflict in Yemen.